Asymmetric labor market institutions in the EMU: Positive and normative implications - Mirko Abbritti; Andreas Mueller (Graduate Institute of International and Development Studies, 2009)
How do asymmetric labor market institutions affect the volatility of innovation and unemployment differentials in a currency union? What are the implications for monetary policy? To answer these questions, this paper sets up a DSGE currency union model with unemployment, hiring frictions and real wage rigidities. The model provides a rigorous but tractable framework for the analysis of the functioning of a currency union characterized by asymmetric labor market institutions. Positively, we find that inflation and unemployment differentials strongly depend on the underlying labor market structures. Moreover, asymmetries in labor market structures increase the volatility of both in.ation and unemployment differentials. Normatively, we find that the optimal in.ation target should give a higher weight to regions with more sclerotic labor markets but with more flexible real wages.
Keywords: E32; E52; F41; 330; currency Union; labor market frictions; real wage rigidities; unemployment; sticky prices; inflation differentials; optimal monetary policy; Arbeitsmarkt; Arbeitsverwaltung; Inflation; Arbeitslosigkeit; Lohnrigidität; Preisrigidität; Geldpolitik; Dynamisches Gleichgewicht; Eurozone; EU-Staaten